2020
DOI: 10.3390/ijerph17051691
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Getting to Sleep and their Association with Emotional and Behavioural Problems in Adolescents: Does the Sleeping Duration Influence this Association?

Abstract: Sleep problems are common in adolescence with a negative impact on the mental health and functioning of adolescents. However, the roles of different sleep problems in relation to emotional and behavioural problems (EBPs), classified according to the 10th version of the International Classification of Diseases as emotional, conduct, hyperactivity and social functioning disorders, are not clear. The first aim of the study was to investigate the association between difficulties in getting to sleep and EBPs in ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 61 publications
0
12
0
6
Order By: Relevance
“…A recent paper from Slovakia found that difficulties in getting to sleep at least once a week, as well as insufficient sleep (less than 8 h), increased the probability of psychosomatic symptoms ( Kosticova et al, 2020 ). Among Canadian adolescents, a later chronotype, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper from Slovakia found that difficulties in getting to sleep at least once a week, as well as insufficient sleep (less than 8 h), increased the probability of psychosomatic symptoms ( Kosticova et al, 2020 ). Among Canadian adolescents, a later chronotype, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…A larger (n = 1472) Canadian survey focusing on school children and youth (5-17 years) showed no differences in terms of sleep quality but reported increased total sleep duration, more evident in adolescents than in children [12]. Sleep disorders are relatively frequent in paediatric populations and are linked to behavioural and emotional problems both in children and adolescents [27][28][29][30]. Isolation imposed during the lockdown may compromise children's ability to successfully regulate behaviour and emotions and consequently there is potential for sleep problems to emerge or worsen [31].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that PIU was positively associated with sleep disorders, which were further related to elevated levels of behavioral/emotional problems. There is existing evidence supporting a strong relationship of PIU with sleep disorders ( Yang et al., 2018 ), as well as evidence that suboptimal sleeping quality increases the likelihood of behavioral/emotional problems ( Kosticova, Husarova & Dankulincova, 2020 ). In addition, we also found that sleep disorders caused more emotional, hyperactive problems, compared to other sub-scales.…”
Section: Discussionmentioning
confidence: 99%